2012
DOI: 10.1258/jrsm.2011.110146
|View full text |Cite
|
Sign up to set email alerts
|

Why UK-trained doctors leave the UK: cross-sectional survey of doctors in New Zealand

Abstract: Objectives To investigate factors which influenced UK-trained doctors to emigrate to New Zealand and factors which might encourage them to return. Design Cross-sectional postal and Internet questionnaire survey. Setting Participants in New Zealand; investigators in UK. Participants UK-trained doctors from 10 graduation-year cohorts who were registered with the New Zealand Medical Council in 2009. Main outcome measures Reasons for emigration; job satisfaction; satisfaction with leisure time; intentions to stay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 4 publications
1
80
0
Order By: Relevance
“…Rather than encouraging immigration of doctors from less developed countries, a policy long regarded as ethically questionable,22 23 UK health strategists should focus on retaining the specialist workforce and attracting ‘home-grown’ junior doctors to pursue EM as a viable career option. Furthermore, expatriate EM doctors may be tempted to return to NHS if new and improved conditions were implemented 24. It is incumbent upon the Department of Health and CEM to continue to negotiate to achieve these improvements, as set out in previous policy documents 14 25…”
mentioning
confidence: 99%
“…Rather than encouraging immigration of doctors from less developed countries, a policy long regarded as ethically questionable,22 23 UK health strategists should focus on retaining the specialist workforce and attracting ‘home-grown’ junior doctors to pursue EM as a viable career option. Furthermore, expatriate EM doctors may be tempted to return to NHS if new and improved conditions were implemented 24. It is incumbent upon the Department of Health and CEM to continue to negotiate to achieve these improvements, as set out in previous policy documents 14 25…”
mentioning
confidence: 99%
“…Scientific literature on migration finds migrant friends and/or relatives to be a strong pulling force for people to emigrate [25][26][27]. The results of our study revealed that students who either strongly agreed or disagreed with the statement viewed emigration as an attractive phenomenon (RE13 on PAtE; Figure 1), while respondents who had no opinion on the question expressed rather neutral attitude towards emigration.…”
Section: Discussionmentioning
confidence: 62%
“…This reflects findings from Goldacre et al who found that the majority of British medical graduates do end up practicing in the NHS in the long term. 23 There appeared to be more barriers to returning to training following taking time out of training abroad. Sharma et al found that of the 1.4% of UK graduates who are practicing abroad in New Zealand, only 30% originally intended to stay, but ultimately 89% planned to permanently emigrate, in part due to better lifestyle and disillusionment with the NHS.…”
Section: Discussionmentioning
confidence: 99%